KUALITAS KIMIA DAN ORGANOLEPTIK SOSIS DARAH TRADISIONAL (TA’BU) KAMBINGYANG DIBERI TAMBAHANPASTA ASAM TAMARIN(Tamarindus indica L.) (Chemical and organoleptik quality of traditional bloodsausages (ta'bu) added tamarind acid paste (Tamarindus indica L.) - Selviana M. Da Costa; Gemini E.M. Malelak; Pieter R. Kale (Universitas Nusa Cendana, 2021)
This study aimed to determine the chemical and organoleptic quality of traditional blood sausage (Ta'bu) that added tamarind acid paste(Tamarindus indica L.) with different level. The materials used were goat blood, mutton, goat abdominal fat, goat liver, grated coconut, black rice flour, tamarind paste, salt, and herbs. Completely randomized design (CRD) 4x3 was used in this experiment. The four treatments consisted of P0; without tamarind paste, P1; tamarind paste 2%, P2; tamarind paste 4% and P3; tamarind paste 6%. The variables measured were content of water, fat, protein, crude fiber, cholesterol, and color, aroma, taste, and texture. Data were analyzed using Kruskal-Wallis ANOVA and non-parametric Kruskal-Wallis. The results showed that the addition of tamarind paste caused the water and fiber content to increase, while the fat and cholesterol content decreased (P<0.01), the texture was moderate to fine and the color varied from light brown to red-brown (P<0.05). The lowest fat and cholesterol content were 13.70% and 83.28% respectively at P3 (6%), and dark brown in colour with texture medium – smooth, or the same as the control. The results of this study concluded that the best addition of tamarind paste was at the 6% level.